Sports Related Dental Trauma in Mixed Dentition in Bucharest - Cătălina Farcașiu; Alexandru-Titus Farcașiu; Aneta Munteanu; Ioana Stanciu; Rodica Luca (Romanian Society of Oral Rehabilitation, 2012)
Children and adolescents present a high risk of dental injury during sports activities. The aim of the study was to gather epidemiological data about dental trauma in mixed dentition children who practice organized sport activities. Material and methods The study group consisted of 348 children (76.43 boys, 23.57% girls) aged 6-13 years, examined in the period January-July 2011 at the Sportsmen Ambulatory in Bucharest. Consent for the examination was obtained from the coaches/parents. Data was statistically analysed using SPSS 10 for Windows (SPSS Inc., Chicago, USA)